Cenozoic intracontinental deformation and exhumation at the northwestern tip of the India‐Asia collision—southwestern Tian Shan, Tajikistan, and Kyrgyzstan. Issue 9 (28th September 2016) - Käßner, Alexandra; Ratschbacher, Lothar; Jonckheere, Raymond; Enkelmann, Eva; Khan, Jahanzeb; Sonntag, Benita‐Lisette; Gloaguen, Richard; Gadoev, Mustafo; Oimahmadov, Ilhomjon
Abstract: Along the Ghissar‐Alai Range of the southwestern Tian Shan (southwestern Kyrgyzstan, northern Tajikistan), the deformation front of the India‐Asia collision—the Pamir‐Tibet orogen—is interacting with the intracontinental Tian Shan orogen without the intervening Tarim Craton. Apatite fission track ( n  = 33, ~3.3–145.6 Ma, 27% <10 Ma) and (U‐Th)/He ( n  = 32, ~1.9–26.1 Ma, 56% <10 Ma) thermochronologic ages suggest approximate isothermal holding (very slow cooling to weak reheating) during relative tectonic quiescence between ~150 and 15 Ma. Accelerated exhumation (~0.2–1.0 km/Myr, median ~0.5 km/Myr) and cooling (11–16°C/Myr) occurred over the last ~10 Myr. Geomorphologic parameters—incision, river steepness, and concavity—confirm the youth of the southwestern Tian Shan's mountain building. High exhumation/cooling rates are correlated with pronounced local relief, produced by Cenozoic faults reactivating inherited (Late Paleozoic) structures. Regions with similarly young exhumation are centered along rims of rigid crustal blocks in the central and eastern Tian Shan. Structurally, the Ghissar‐Alai Range is a broad, east trending zone of dextral transpression that includes the northern Tajik Basin (Illiak Fault Zone) and the Pamir Thrust System of the frontal northern Pamir. It is the particular deformation field at the northwestern tip of the India‐Asia collision—the interaction of the westward gravitational collapse of the Pamir Plateau into the Tajik Basin with the bulk northward motion of the Pamir—that transformed the southwestern Tian Shan into a dextral transpression belt. The dextral transpression in the southwestern Tian Shan contrasts with sinistral strike‐slip shear localized along inherited fault zones, accommodating dominant north‐south shortening, in the central and eastern Tian Shan. The deformation field influenced by the Pamir and the associated young exhumation make the Ghissar‐Alai Range a unique feature in the Tian Shan orogen. Key Points: Southwestern Tian Shan shows tectonic quiescence between ~150 and 15 Ma and accelerated exhumation/cooling over the last ~10 Myr Gravitational collapse of the Pamir Plateau into the Tajik Basin affected the SW Tian Shan and induced a belt of dextral transpression Southwestern Tian Shan is an integral part of the Pamir‐Tibet deformation field rather a distinct intracontinental orogen